Improving Physical and Recreation Health Education Competence Through Android-Based Teaching Media in Rhythmic Activities - Eva Faridah; Indra Kasih; Sinung Nugroho; Onyas Widianingsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study seeks to evaluate the impact of Android-based teaching tools on enhancing the skills of Physical Health And Recreation Education students, particularly in rhythmic activity courses for the upcoming academic year 2022/2023. This study follows the research conducted by Borg and Gall across 10 stages. The research will be conducted at the Faculty of Sports Science, Universitas Negeri Medan. This research was conducted over one semester, specifically from May to June 2023. This study focuses on students of the Physical Health And Recreation Education programme who are enrolled in a rhythmic activity gymnastics course during the fifth semester of the 2022/2023 academic year, totaling 115 students. A modest sample size of 30 students, contrasted with a more substantial sample of 50 students. Conducting data collection involves distributing questionnaires to small samples, large samples, and comparison samples, as well as consulting material experts and learning media experts. Based on the statistical analysis, the trial using an android-based media for rhythmic gymnastics demonstrated a significant improvement in students' competence, with a p-value of 0.000. Graduation competencies in rhythmic gymnastics for students, particularly the fundamental movements they possess prior to utilising an android-based rhythmic gymnastics learning tool, demonstrate a notable improvement. Lecturers are adept at utilising teaching media to enhance learning.